2020
DOI: 10.3348/kjr.2019.0797
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Tumor Regression Grade on MR in Rectal Cancer: A Large-Scale, Single-Center Experience

Abstract: Objective To determine the prognostic value of MRI-based tumor regression grading (mrTRG) in rectal cancer compared with pathological tumor regression grading (pTRG), and to assess the effect of diffusion-weighted imaging (DWI) on interobserver agreement for evaluating mrTRG. Materials and Methods Between 2007 and 2016, we retrospectively enrolled 321 patients (male:female = 208:113; mean age, 60.2 years) with rectal cancer who underwent both pre-chemoradiotherapy (CRT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 30 publications
0
20
1
Order By: Relevance
“…The high recurrence rate of 30% specified distant and local recurrences, the relatively advanced stage of LARC with dMMR versus pMMR at the beginning of nCRT (clinical T4:26.7% vs. 9.2%; M1:23.3% vs. 6.3%). TNM stage, especially T4, is likely more important as a prognostic factor than tumor regression ( 12 ). Nevertheless, similar TRG rates were gradually caught up after nCRT in our study, and the improvement might build a solid foundation for good subsequent OS despite an R0 resection rate of 90% with dMMR instead of 100% with pMMR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high recurrence rate of 30% specified distant and local recurrences, the relatively advanced stage of LARC with dMMR versus pMMR at the beginning of nCRT (clinical T4:26.7% vs. 9.2%; M1:23.3% vs. 6.3%). TNM stage, especially T4, is likely more important as a prognostic factor than tumor regression ( 12 ). Nevertheless, similar TRG rates were gradually caught up after nCRT in our study, and the improvement might build a solid foundation for good subsequent OS despite an R0 resection rate of 90% with dMMR instead of 100% with pMMR.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a capecitabine-containing regimen was used for nCRT and adjuvant chemotherapy (capecitabine based CT). Several studies (12,16,17) have shown that early TRG downstaging can predict patient prognosis with comparable performance for OS and DFS. Based on these data, we attempted to identify the clinicopathological characteristics at baseline that are likely to be associated with tumor downstaging.…”
mentioning
confidence: 99%
“…When 28 original research studies reporting HR published in the Korean Journal of Radiology in 2020–2021 [ 11 15 32 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 ] were evaluated against a rigorous standard, 96.4% (27/28) explicitly defined the events for HR, 48.1% (13/27) unmistakably described the reference category for HR calculation for categorical variables, and only 50% (10/20) clearly described the one-unit amount for HR for continuous variables. Therefore, further improvements are required.…”
Section: How To Report Hrmentioning
confidence: 99%
“…Study characteristics and methodological details are shown in Tables 1 and 2 and Supplemental Tables 4-10 (Supplemental material available online). Combined, 19 studies investigated T2-mrTRG (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43), 39 studies investigated DW-MRI (25,32,37,, 13 studies investigated PW-MRI (80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92), and 15 studies investigated endoscopy with or without MRI (26,36,(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The PPV and NPV of T2-mrTRG grade 1 for detecting ypCR were in the range of 0%-99% and 73%-98%, respectively. The majority of studies (n = 17) were conducted retrospectively (25,(27)(28)(29)(30)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Sample sizes were in the range of 41-439 patients.…”
Section: T2-weighted Mrtrg Scoring Systemmentioning
confidence: 99%